EVALUATING FRONTAL SINUS OPACIFICATION SEVERITY USING THE LUND-MACKAY SCORE BASED ON ANATOMICAL VARIANTS OF POSTERIOR FRONTAL RECESS CELLS THROUGH IMAGING ANALYSIS (Tạp chí Y học Cộng đồng, 2026)
Objectives: To determine the prevalence of posterior frontal recess cells (suprabulla cell, suprabulla frontal cell, and supraorbital ethmoid cell) and evaluate their association with frontal sinus opacification on computed tomography.Subjects and methods: A cross-sectional descriptive study with analysis was conducted on 174 patients (340 sides) at Gia Dinh Peoples’s Hospital from January 2024 to June 2025. Posterior wall cell variants were identified on multiplanar CT scans and correlated with frontal sinus opacification status according to the Lund-Mackay score.Results: The suprabulla cell was the most common posterior variant with a prevalence of 59.7%, followed by the suprabulla frontal cell at 25.0% and the supraorbital ethmoid cell at 7.4%. Statistical analysis showed that the presence of the suprabulla frontal cell was associated with a significantly higher rate of frontal sinus opacification (45.9%) compared to its absence (20.0%), with an odds ratio (OR) of 3.39 (95% CI: 1.90–6.06; p < 0.001). In contrast, no statistically significant association was found between the presence of the suprabulla cell (p = 0.330) or the supraorbital ethmoid cell (p = 0.442) and frontal sinus opacification.Conclusion: The suprabulla frontal cell was significantly associated with frontal sinus opacification on computed tomography. Accurate preoperative identification of this cell on multiplanar imaging may help optimize frontal recess surgical planning.
Keywords: suprabulla cell, suprabulla frontal cell, supraorbital ethmoid cell, frontal recess, frontal sinusitis, computed tomography.